A link between transcription fidelity and pausing in vivo. Issue 2 (15th March 2017) - Gamba, Pamela; James, Katherine; Zenkin, Nikolay
ABSTRACT: Pausing by RNA polymerase is a major mechanism that regulates transcription elongation but can cause conflicts with fellow RNA polymerases and other cellular machineries. Here, we summarize our recent finding that misincorporation could be a major source of transcription pausing in vivo, and discuss the role of misincorporation-induced pausing.